Capacity Payments in the Turkish Electricity Market: A Necessity or Policy? - Korucan, Aysun; Yardimci, Okan (International Journal of Energy Economics and Policy, 2023)
Capacity mechanisms have been implemented in different forms for various purposes. Contrary to altering trends in the electricity markets, Türkiye opted for enforcing “capacity payments,” regarded as a primitive form of the mechanisms to ensure the security of supply and system reliability. This study mainly aims to build a critical review of the Turkish capacity mechanism design. The survey conducted makes valuable inferences along with the opinions of different stakeholders. The results indicate that the current capacity payment scheme, a non-market based, is not sustainable in the long run. Therefore, improving the existing payment methodology by reconsidering mechanism’s scope and different age criteria, efficiency, and deliverability for plants or implementing other types of mechanisms with a market reform, such as demand response participation, seems more efficient.